Borboletas frugívoras na Mata Atlântica do Litoral Sul da Bahia: estrutura de comunidade e biologia de Opsiphanes quiteria meridionalis Staudinger (Nymphalidae: Brassolini) - Neves, Dorisane Almeida (2015)
The community of frugivorous butterflies can be used as environmental indicators. That group is a valuable tool for the development of conservation plans in the biomes of Brazil. Likewise, morphological studies covering intraspecific and interspecific variation of the immature stages, providing support to strengthen the systematics and taxonomy. This study aimed to analyze the structure of the community of frugivorous butterflies in Atlantic Forest on the south coast of Bahia and describe the biology and the external morphology of the immature stages of Opsiphanes quiteria meridionalis Staudinger, 1887, including chaetotaxy. The butterflies were sampled in three different habitats, between the months of October 2013 to March 2014, with Van Someren-Rydon trap. In 8,640 hours/trap were collected 523 individuals belonging to 59 species and 5 subfamilies of Nymphalidae, with 17 new records for the state of Bahia and 11 for Northeast. Satyrinae was the group with the highest abundance and richness. The biology and external morphology of the immature stages of Opsiphanes quiteria meridionalis Staudinger were described from oviposition and development in the laboratory. Leaves of Dypsis lutescens H. Wendl (Arecaceae), ornamental plant, were used in the feeding of larvae. Egg stage average duration of 7.2 days. Larval stage had five instars with an average duration of 48.5 days and the pupa 16.5 days. The results obtained in this study indicates that the EEEWG an expressive richness to the northeast and O. q. meridionalis presents basic characters of Brassolini (Morphinae).